2009
DOI: 10.1016/j.cub.2009.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Signaling in the Endodermis Controls Arabidopsis Root Meristem Size

Abstract: Plant growth is driven by cell proliferation and elongation. The hormone gibberellin (GA) regulates Arabidopsis root growth by controlling cell elongation, but it is currently unknown whether GA also controls root cell proliferation. Here we show that GA biosynthetic mutants are unable to increase their cell production rate and meristem size after germination. GA signals the degradation of the DELLA growth repressor proteins GAI and RGA, promoting root cell production. Targeting the expression of gai (a non-GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
278
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 370 publications
(302 citation statements)
references
References 35 publications
23
278
0
1
Order By: Relevance
“…This observation is in accordance with many studies where similar criteria to determine the RAM/EZ boundary have been used, and which report meristem length increase beyond 5 d after germination (DAG) and later (Galinha et al, 2007;Ubeda-Tomas et al, 2009;Gonzalez-Garcıa et al, 2011;Makkena and Lamb, 2013). Moreover, a kinematic analysis of the arabidopsis root showed that accelerated root growth is mainly due to an increased cell production rate during the first 14 DAG and a steady increase in meristem length during the first 2 weeks of growth after germination (Beemster and Baskin, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…This observation is in accordance with many studies where similar criteria to determine the RAM/EZ boundary have been used, and which report meristem length increase beyond 5 d after germination (DAG) and later (Galinha et al, 2007;Ubeda-Tomas et al, 2009;Gonzalez-Garcıa et al, 2011;Makkena and Lamb, 2013). Moreover, a kinematic analysis of the arabidopsis root showed that accelerated root growth is mainly due to an increased cell production rate during the first 14 DAG and a steady increase in meristem length during the first 2 weeks of growth after germination (Beemster and Baskin, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Primer sequences are indicated in Table EV1. The CYCB1;1 construct was described in Ubeda‐Tomás et al (2009). …”
Section: Methodsmentioning
confidence: 99%
“…In roots, the average cell cycle duration is constant, and changes in cell production rates are mostly due to changes in the number of dividing cells and thus in the meristem size (Baskin, 2000). Correspondingly, DELLAs induce cell differentiation in the root, thereby making the root meristem smaller and thus decreasing cell production rates (Achard et al, 2009;Ubeda-Tomás et al, 2009;Moubayidin et al, 2010). Recently, the average cell cycle duration in leaves was reported to be constant throughout leaf development as well; therefore, the observed decrease in cell production rates during development is the consequence of a decrease in the fraction of proliferating epidermal cells due to the transition to cell expansion (Asl et al, 2011).…”
Section: Dellas Control Cell Proliferation By Inducing Differentiationmentioning
confidence: 99%
“…The 35S::gai-GR construct was made based on a SCR::gai-GR-YFP construct (Ubeda-Tomás et al, 2009), kindly donated by Malcolm Bennett (University of Nottingham), by amplifying gai-GR and cloning this into the Gatewaycompatible pK7WG2 vector (Karimi et al, 2002), and transformed into Columbia-0 plants using Agrobacterium tumefaciens strain C58C1 pMP90. RGA::GFP-RGA, rga-28, and rga-28 gai-2 seeds were kindly provided by Prof. Dr. Tai-ping Sun (Duke University).…”
Section: Transgenic Lines and Mutantsmentioning
confidence: 99%